2021
DOI: 10.1111/peps.12446
|View full text |Cite
|
Sign up to set email alerts
|

Admired and disgusted? Third parties’ paradoxical emotional reactions and behavioral consequences towards others’ unethical pro‐organizational behavior

Abstract: Unethical pro-organizational behavior (UPB) is often visible to co-workers; however, reactions to UPB are rarely considered in empirical research in spite of their importance to the social dynamics in the workplace. Drawing upon appraisal theory of emotion and the behavioral ethics literature, we predict that observing UPB would lead third parties to experience admiration due to the pro-organizational nature of UPB; these third parties would in turn be motivated to display more helping behavior towards the UPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 181 publications
1
41
2
Order By: Relevance
“…A benefit of the full-cycle research approach that we undertook in this article is that, while any given study may have limitations, those limitations are often balanced out by another study (e.g., Tang, Koopman, et al, 2021; Tang et al, 2022). For example, despite the many strong elements of our ESM study (time separation for most variables, controlling for cyclical variation, and using other-sourced data), a limitation is that political correctness and depletion were measured at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…A benefit of the full-cycle research approach that we undertook in this article is that, while any given study may have limitations, those limitations are often balanced out by another study (e.g., Tang, Koopman, et al, 2021; Tang et al, 2022). For example, despite the many strong elements of our ESM study (time separation for most variables, controlling for cyclical variation, and using other-sourced data), a limitation is that political correctness and depletion were measured at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, we integrate the W-HR model with social identity theory and identify an important boundary condition in the work-family enrichment process. We propose that occupational identity is a key personal resource (ten Brummelhuis & Bakker, 2012) that can augment the work-family enrichment process. While meta-analytic research has shown that employees who identify more closely with their occupations spent more time at work (Ng & Feldman, 2008), which could impair relationshipbased family performance, our research attempts to broach this conundrum through a different perspective, by highlighting how high occupational identity could potentially facilitate work-family enrichment and has positive implications for the work-family dynamic-specifically, we propose that for service providers who identify more strongly with their occupations, this occupational identification would serve as a key personal resource (in the W-HR model), such that they are more likely to benefit from receiving gratitude at work, in the form of heightened relational energy, that spills over to the family.…”
Section: Between-personmentioning
confidence: 99%
“…For example, gratitude from others may translate into a better relationship with different stakeholders in the organization (Algoe, 2012), as gratitude is noted to be important for the development and maintenance of social relationships (e.g., Kubacka et al, 2011). For example, gratitude from others may translate into a better relationship with different parties in the organizations (Algoe, 2012), or even evoke moral emotions (McCullough et al, 2001), as gratitude is noted to be important for psychological well-being and moral decision making (e.g., DeSteno et al, 2010;Kubacka et al, 2011;Tang et al, 2020Tang et al, , 2021.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Recent work by Tang et al. (2021) has expanded the UPB literature by shifting focus from the perpetrators of UPB to third‐party observers. Their work highlighted those third parties who observed prosocial unethical behavior directed toward the organization experienced both admiration and disgust, with the level of disgust dependent on the observers’ moral attentiveness.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Our research expands the conversation on prosocial forms of unethicality, such as unethical pro‐organizational behavior (UPB; Umphress et al., 2010) and pro‐group unethical behavior (Thau et al., 2015), by bringing the phenomenon to a dyadic level and shifting focus to the recipient of the behavior. Given that prior work has focused on the provider or third‐party observers (Tang et al., 2021) of prosocial unethical behavior toward the organization or group, it does not provide insight into the social exchange dynamics at the heart of our model. Our application and extension of social exchange theory indicates that PCUB induces an obligation to reciprocate that strengthens the social exchange relationship while also inducing lower perceptions of the provider's integrity that harm the social exchange relationship.…”
Section: Introductionmentioning
confidence: 99%